Pola Penggunaan dan Pengetahuan Pasien Mengenai Penggunaan Obat Anti Inflamasi Non Steroid di Apotek Perdana Yogyakarta - Qarriy Aina Urfiyya; Zelva Desvandria Arjuliant (CERATA Jurnal Ilmu Farmasi, 2024)
Non-steroidal anti-inflammatories (NSAIDs) are drugs used to treat pain, especially joint pain. The prevalence of joint disease in Yogyakarta is quite high, at 5.93%, so the use of AINS is also high. However, there are still many people who do not understand the proper use of AINS. This study aims to determine the description of patient knowledge about AINS at Perdana Yogyakarta Pharmacy. This study used a descriptive observational method using a questionnaire. Sampling using purposive sampling technique on 72 respondents. Data analysis includes respondent characteristics, drug use patterns, and level of knowledge about AINS which are then grouped into good, sufficient, and deficient categories. SPSS analysis was used to determine the relationship between respondent characteristics and knowledge about AINS. Respondents who used AINS drugs were mostly aged 45-59 years (44%), female gender (65%), and non-smoking (85%). As many as 47% of respondents sometimes experience gastric symptoms. This study concludes that the most widely used AINS drug is diclofenac (49%), and most respondents have a good (44%) and sufficient (44%) level of knowledge about the use of AINS drugs.